Автоматизированные комплексы для биомеханических исследований в ортопедии - Бых, А. И.; Карпинский, М. Ю. (ХНУРЭ, 2008)
Complexes for biomechanical researches are an effective remedy of an estimation of a condition of a locomotorium of the person. The instance of construction of similar complexes, the block diagramme of a design and the block the software circuit design is in-process resulted
Keywords: ортопедия; биомеханические исследования